“Fim dos tempos - o último game show do mundo": a produção remota de um game show para a internet - Cozaro, Rafael dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Este trabalho é um projeto experimental do curso de “Rádio, TV e Internet” e consiste na criação e exibição do game show ao vivo “Fim dos Tempos - O Último Game Show do Mundo”, programa exibido ao vivo na plataforma Twitch de maneira remota, ou seja, sem a necessidade de um encontro presencial entre a equipe envolvida. Passando pelo processos da produção audiovisual, esse trabalho tratará de todas as etapas, desde a idealização até a postagem do produto final editado. O programa foi exibido no dia 22 de dezembro de 2023 e teve 40 minutos de duração. O programa pode ser assistido no link: http://youtu.be/mGV9nbGvnFI

This work is an experimental project of the course "Radio, TV and Internet" and consists in the creation and airing of the live game show “End of Times - The Last Game Show of the World”, a program broadcasted live on the Twitch platform in a remote way, that is, without the need of a physical meeting between the involved team. Passing through the audiovisual production processes, this work will treat all stages, from the ideation until the posting of the final edited product. The program was broadcasted on the 22nd of December of 2023 and had 40 minutes of duration. The program can be watched on the link: http://youtu.be/mGV9nbGvnFI
"End of times - the last game show on earth": remote production for the internet
Keywords: Game show; Internet; Covid-19; Streaming